Drowsiness detection for car assisted driver system using image processing analysis-interfacing with hardware - Huong, Nice Quan (2010)
The purpose of this study is to detect drowsiness in drivers to prevent accidents and to improve safety on the highways. A method for detecting drowsiness/sleepiness in drivers is developed by using a camera that point directly towards the driver’s face and capture for the video. Once the video is captured, monitoring the face region and eyes in order to detect drowsy/fatigue. The system able to monitoring eyes and determines whether the eyes are in an open position or closed state. In such a case when drowsy is detected, a warning signal is issued to alert the driver. It can determine a time proportion of eye closure as the proportion of a time interval that the eye is in the closed position. If the driver’s eyes are closed cumulatively more than a standard value, the system draws the conclusion that the driver is falling asleep, and then it will activate an alarm sound to alert the driver